INTERNATIONAL LEGAL STANDARDS OF PERSONAL AUTONOMY IN ACADEMIC CULTURE AND SCIENTIFIC COOPERATION - Yurii Sheliazhenko (Міжнародні відносини: теоретико-практичні аспекти, 2020)
This study is relevant to global discussions concerning freedom of research in view  of transformations  in science effectiveness evaluation, funding  and  research organization, as well as Ukrainian context of educational reform. Main objectives of the article are to study international legal standard of personal autonomy in scientific life and academic culture, the role of personal autonomy in Ukraine's global scientific and technical cooperation development. Methods of analysis and synthesis are used to study legal relations and normative guarantees of personal autonomy in academic culture and scientific cooperation. Comparison method is used to identify common and distinct problems in the development of scholars' personal autonomy in Ukraine and in the world. In conclusion, international legal standards of personal autonomy in academic culture and scientific cooperation prescribe imperative of individual and institutional   independence   and   responsibility   in   the   search   and   transfer   of knowledge, demands respect for the freedom of scientific research, academic communication, and expression of views. This standard is connected with human dignity, the goal of education to develop human abilities to control own life, to be a successful and happy citizen in a democratic information society. Self-organization of scientists helps to overcome threats to personal autonomy, such as academic dishonesty, monopolism, paternalism, formalism, and bureaucracy. New Ukrainian law on education creates instruments for combating academic dishonesty and allows initiatives   for   science   and   education   improvement,   although   administrative regulations still impose controversial standards of scientific quality, for example, the requirement  of  publications  in  periodicals  indexed  by  scientometric  databases Scopus or Web of Science to confer academic rank. Ukrainian academic culture needs modernization to raise the scientific research and create the basis of a competitive innovative   economy.   It   is   necessary   to   develop   the   Ukrainian   infrastructure of scientific   information,   including   scholarly   publishers,   indexes,   and   libraries,to strengthen    legal    guarantees    of    personal    autonomy,    to    support    projects of international scientific and technical cooperation, application of scientific results in economics and social life. So, the significance of study in formulated proposals and predictions regarding pragmatic liberalization of scientific life in Ukraine.